Peran Artificial Intelligence (AI) dalam Menunjang Kinerja Tutor di Pusat Kegiatan Belajar Masyarakat (PKBM) Melati Kabupaten Enrekang - Selistiawati; Saidang; Haerusman; Baharuddin; M. Hatta (Mataram University, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant changes to the education sector, including nonformal education. As a technology that can support learning planning, implementation, and evaluation, AI has the potential to enhance tutor performance and improve the quality of learning. This study aims to describe the forms of AI utilization in learning, analyze its impact on tutor performance, and identify the factors influencing its use at PKBM Melati, Enrekang Regency. This research employed a descriptive qualitative approach. Data were collected through interviews, questionnaires, and documentation. The research informants consisted of one manager and five tutors, while eight learners were involved as supporting respondents. Data analysis was carried out through the stages of data condensation, data display, and conclusion drawing. The results indicate that AI is used by tutors to help prepare learning instruments, develop teaching materials, search for learning references, design evaluations, and support more systematic learning delivery. The use of AI improves tutors' work efficiency, streamlines learning administration, and enhances the quality of material delivery, making it more interactive and easier for learners to understand. The factors influencing AI utilization include the availability of technological facilities, institutional support, training activities, perceived ease of use, and perceived usefulness experienced by tutors. Therefore, the use of AI positively contributes to supporting tutor performance and improving the quality of learning at PKBM Melati, Enrekang Regency.